Avoiding Armageddon America, India, and Pakistan to the brink and back - Riedel, Bruce O. (Brookings focus books, 2013)
"Traces the history of the United States, India, and Pakistan as British colonies and their interaction in the twentieth and twenty-first centuries, particularly in regard to relations between India and Pakistan, nuclear proliferation, the global jihad movement, and U.S. diplomatic efforts to stabilize conditions on the subcontinent"--Provided by publisher.